TEVAR FOLLOWING A PENETRATING AORTIC ULCER COMPLICATED WITH A LATE PSEUDOANEURYSM FORMATION - Marinho, Andre (2018)
Introduction: The thoracic aortic diseases are a major cause contributing to the high mortality rate of the cardiovascular disease. Recent high resolution radiologic studies have allowed us to get new perspectives related to their etiopathogenesis and the different stages of the acute aortic syndrome (AAS). Clinical case: This case report is about a 51 years old male patient that was referred to the ER with a sudden, acute and abrupt thoracic pain with dorsal irradiation. Also associated were high blood pressure values. An angioCT was immediately performed which showed a penetrating aortic ulcer (PAU) at the descending thoracic aorta with a parietal thickening (suggestive of intramural hematoma — IMH). After 72h of best medical treatment a new angioCT was done which was overlapping. So, it was decided to discharge the patient at the fifth day of hospital stay. At 6 months a new CT was done, this time showing regression of the intramural hematoma but a progression of the PAU to a false aneurysm. Given the new findings it was decided to perform a thoracic endovascular repair. The patient was, then, discharged at the second post-operative day without symptoms with an angioTC showing successful exclusion of the lesion without further complications. Discussion and Conclusion: The PAU usually results from the erosion of an atherosclerotic plaque which can then be complicated by an IMH, pseudoaneurysm formation or progression to an aortic dissection or rupture. It should be noted that the evolution and subsequent natural history of these pathologies remains, still, not totally clear. The clinical report hereby described reinforces the understanding of the IMH, the PAU and the aortic dissection as different stages of the same disease. We hope to see, in the future, new data related to this disease pathophysiology and respective treatment.